2018
DOI: 10.1186/s12889-018-6285-9
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of Ghanaian patients to the reporting of adverse drug reactions: a quantitative and qualitative study

Abstract: BackgroundUnder-reporting of adverse drug reactions (ADRs) is a major challenge for pharmacovigilance in Africa. This study sets out to assess the level of awareness of Ghanaian patients about ADRs and ADR-reporting and explores how different patients in Ghana recognize an ADR and the steps they take when they experience an ADR.MethodsThis was a two-part study consisting of a survey to quantify the awareness of Ghanaian patients on ADRs and ADR-reporting, and in-depth interviews to explore how patients recogni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 30 publications
1
28
0
Order By: Relevance
“…As studies showed that consumers needed more steps to identify their symptoms as ADRs than HCPs [ 19 ], we incorporated the knowledge or ability to recognise ADRs into our conceptual framework reflecting consumers’ perspectives. Based on the framework, five questions were formulated, addressing the objective knowledge of ADRs [ 19 , 26 ]. For the case of knowledge about SR, the questions about their awareness of the SR system and the relief scheme supported by the Korean government were included and the questions that measure self-efficacy, indicating perceived ability to spontaneously report, were considered.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…As studies showed that consumers needed more steps to identify their symptoms as ADRs than HCPs [ 19 ], we incorporated the knowledge or ability to recognise ADRs into our conceptual framework reflecting consumers’ perspectives. Based on the framework, five questions were formulated, addressing the objective knowledge of ADRs [ 19 , 26 ]. For the case of knowledge about SR, the questions about their awareness of the SR system and the relief scheme supported by the Korean government were included and the questions that measure self-efficacy, indicating perceived ability to spontaneously report, were considered.…”
Section: Methodsmentioning
confidence: 99%
“…As studies showed that consumers needed more steps to identify their symptoms as ADRs than HCPs [19], we incorporated the knowledge or ability to recognise ADRs into our conceptual framework reflecting consumers' perspectives. Based on the framework, five questions were formulated, addressing the objective knowledge of ADRs [19,26].…”
Section: Questionnaire Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar findings have been reported in previous studies in Ghana. 23,24 Lack of patient reporting of ADRs may result from failure by health professionals to provide adequate information on drug safety to patients. 21 For the same reason, patients believe that it is a waste of time to complete the form on their own.…”
Section: Discussionmentioning
confidence: 99%
“…The patient is partner in PRN medicines management and can be involved in recognising and reporting symptom improvements, medications’ side effects and adverse reactions. Additionally, he/she should be motivated, informed and educated on how to report them, and how their reports lead to the improvement of the medication process [ 70 , 71 ], wellbeing and healthcare outcomes [ 72 , 73 ].…”
Section: Ethics and Prn Medicines Managementmentioning
confidence: 99%